(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This extended annotation provides an in-depth overview of non-traditional methods of assessing young children and their significance in contemporary early childhood education. As traditional assessment techniques often rely on standardized tests and structured tasks that may not accurately reflect a child’s holistic development, educators increasingly turn to more flexible and child-centered approaches. Non-traditional assessment methods—such as systematic observation, portfolio assessment, project-based evaluation, play-based assessment, interviews, checklists, anecdotal records, and performance tasks—allow teachers to gather comprehensive information about children’s cognitive, social, emotional, linguistic, and motor skills.